EFFECTIVENESS OF AL-QURAN THERAPY IN REDUCING THE LEVEL OF AUDITORY HALLUCINATIONS - Fikri, Zahid; 'Ibad, Muhammad Rosyidul; Arfianto, Muhammad Ari; Mu'jizah, Khikmatul; Setyowati, Lilis; Ardiana, Tessa Gustin; Putri, Evita Muslima Isnanda; Choirulloh, Achmad (Universitas Airlangga, 2024)
Introduction: Auditory hallucinations, which involve hearing voices that are not present, can severely impact an individual’s mental health and quality of life if left untreated. Qur'anic therapy, which involves reciting verses from the Qur’an, is believed to help calm the mind and reduce hallucination symptoms. The purpose of this community service initiative is to teach staff and patients to incorporate Qur'anic therapy into their daily routines, supporting both spiritual and psychological healing. Methods: This community service was conducted at the Pasuruan Social Rehabilitation Home with 35 clients experiencing auditory hallucinations who were coherent, cooperative, and Muslim. The aim was to provide Al-Quran therapy for 2 weeks, with each session lasting 5 minutes. The effectiveness of the therapy was measured using self-reported frequency of hallucinations and staff observations, with data analyzed through a paired sample t-test or Wilcoxon signed-rank test, depending on the distribution, to assess any significant reduction in the auditory hallucinations. Results: Some of the results experienced by patients after receiving Al-Quran therapy are that patients are more peaceful when experiencing auditory hallucinations. The patient also said that reading the Al Quran could be a distraction when the patient had auditory hallucinations. On average, 60% of patients' hallucinations were mild, 37.1% were moderate, and 2.9% had severe hallucinations. Conclusion: These findings indicate that Al-Quran therapy can be used as an effective method to reduce the frequency of auditory hallucinations in schizophrenia patients at the Pasuruan Social Rehabilitation Home. These findings have important implications for the management and care of patients with auditory hallucinations, as well as providing a therapeutic alternative that can improve patients' quality of life.